2011
DOI: 10.5251/abjna.2011.2.4.693.697
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics, phytochemicals and mineral composition of Ocimum gratissimum applied with Albit® bioproduct

Abstract: Ocimum gratissimum (basil) was seed-dressed and foliar sprayed with Albit® bioregulator/biopesticide and assessed for its growth characteristics, phytochemicals and mineral composition. Those applied with Albit ® had increased number of leaves (two/ plant), increased shoot height (2cm/plant) at 28 days after sowing (DAS), increased shoot weight (7.4g/plant) and roots weight (3g/plant) at 182 DAS than the control without Albit ® application. Albit ® application induced flowering 15 days earlier than those in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Presence of principal phytoconstituents like alkaloids, glycosides, tannins, phenolic compounds, saponin, avonoids, terpenoids, steroids, sterols, saponins, avones and avonoids from aqueous and alcoholic leaf extracts of O. gratissimum L.has been previously reported (Anjorin and Ugwu 2011;Choudhury et al 2011). The antioxidant property of O. gratissimumwas reported and co-related with its phytochemical constituents previously (Sulistiarini 1999;Dubey, Tiwari and Mandin 2000;Holets et al 2003).…”
Section: Discussionmentioning
confidence: 71%
“…Presence of principal phytoconstituents like alkaloids, glycosides, tannins, phenolic compounds, saponin, avonoids, terpenoids, steroids, sterols, saponins, avones and avonoids from aqueous and alcoholic leaf extracts of O. gratissimum L.has been previously reported (Anjorin and Ugwu 2011;Choudhury et al 2011). The antioxidant property of O. gratissimumwas reported and co-related with its phytochemical constituents previously (Sulistiarini 1999;Dubey, Tiwari and Mandin 2000;Holets et al 2003).…”
Section: Discussionmentioning
confidence: 71%
“…It is a biological preparation based on bacteria (Bacillus megaterium) (Gins et al, 2017). It has been suggested that Albit®, which increases seed germination percentage, seedling growth and plant growth, has been developed as an environmentally friendly product that can be an alternative to synthetic fertilizers and fungicides (Anjorin et al, 2011). Unlike synthetic preparations such as indole acetic acid, indole butyric acid, gibberellic acid, which are frequently used in plant growing, it contains biofungicide, biological fertilizer and anti-stress agent (Anjorin et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…com). It is known to improve seed germination and plant growth, and induce early flowering [11], [12]. Additionally, some positive sideeffects of Albit ® have been described in the literature.…”
mentioning
confidence: 99%